Electric double-layer capacitors with corn starch-based biopolymer electrolytes incorporating silica as filler - Teoh, K.H.; Lim, C.S.; Liew, C.W.; Ramesh, S.; Ramesh, S. (Springer Verlag (Germany), 2015)
Solid-state electric double-layer capacitors (EDLCs) based on corn starch biodegradable polymer electrolytes are fabricated. Silica is added into the corn starch polymer electrolytes to improve the ionic conductivity and capacitance of the EDLCs. The ionic conductivity as a function of temperature obeys the Arrhenius equation indicating ionic hopping mechanism in the polymer electrolytes. Linear sweep voltammetry shows that the prepared corn starch-based biopolymer electrolyte is stable in the range from −2.5 to 2.5 V. Electrical capacitance performances of these capacitors are studied by cyclic voltammetry, galvanostatic charge–discharge, and AC impedance spectroscopy. The discharge characteristics have been found to be almost linear, which confirms the capacitive behavior of the EDLC cell. The fabricated EDLC cells perform good cyclability up to 500 cycles with more than 90 % of coulombic efficiency.